Aromatic hydrocarbon compound degradation of phenylacetic acid by indigenous bacterial Sphingopyxis isolated from Lake Taihu. Issue 22 (17th November 2019) - Huang, Feiyu; Li, Xiaoyu; Guo, Jian; Feng, Hai; Yang, Fei
ABSTRACT: The aromatic compound phenylacetic acid (PAA) is present in the environment, and released in the catabolism of phenylalanine, 2-phenylethylamine, or environmental contaminants such as ethylbenzene and styrene. PAA was also proposed to be involved in human chronic kidney disease development. Several bacteria and fungi utilize these aromatic acids as sole carbon source either during aerobic or anaerobic conditions. The aromatic structure of PAA makes this compound resistant toward oxidation or reduction, because the stabilizing resonance energy of the aromatic ring system is difficult to overcome. In the case of bacteria that utilize aromatic compounds as growth substrates, the aromatic ring system limits survival due to a lack of carbon source. Sphingopyxis sp. YF1 isolated from Lake Taihu was found to be beneficial in bioremediation of aromatic compounds. This study thus aimed to examine the influence of environmental factors such as temperature, PAA concentration, and pH on the effectiveness of Sphingopyxis sp. YF1 to degrade aromatic compounds using PAA as model compound. Data showed the highest PAA-degrading rate of strain Sphingopyxis sp. YF1 was 7.6 mg/L·h under the condition of 20°C, pH 9 with a 1000 μg/ml concentration of PAA. Evidence indicates that PAA-degrading ability of strain Sphingopyxis sp. YF1 appears to be primarily influenced by the concentration of PAA, followed by temperature and pH. PAA-degrading gene PAAase was identified in this strain using polymerase chain reaction (PCR) method. These results illustrate that the bacteria Sphingopyxis sp. YF1 removes PAA effectively at certain environmental conditions and this proves beneficial in bioremediation of aromatic compounds.